SPP1 promotes cisplatin resistance in cervical cancer by regulating KRAS expression - Changchun Long; Shiqi Wang; Yiyong Wang (PLoS ONE, 2026)
Background Chemotherapy resistance is a major treatment issue for cervical cancer (CC), contributing to high morbidity and mortality. This study identifies key molecular drivers of CC progression and cisplatin (DDP) resistance, focusing on secreted phosphoprotein 1 (SPP1). Methods Differentially expressed genes (DEGs) were identified from TCGA-CC and GSE46857 datasets. Protein-protein interaction network analysis and topological ranking determined candidate genes. SPP1 expression was evaluated in CC cell lines using qPCR and Western blotting. Cisplatin-resistant CC cells were used to examine SPP1’s role in drug resistance. Functional assays assessed cell proliferation, apoptosis, migration, and invasion. Results Bioinformatics analysis identified SPP1 as a hub gene upregulated in CC. SPP1 expression was higher in CC and DDP-resistant cells. Silencing SPP1 inhibited cell growth and enhanced apoptosis, while overexpression had the opposite effects. Silencing SPP1 enhanced DDP sensitivity, while overexpression reduced DDP cytotoxicity. Mechanistically, SPP1 positively correlated with KRAS expression, and KRAS modulation partially reversed SPP1’s effects on DDP resistance. Conclusion SPP1 is upregulated in CC and DDP-resistant cells, promoting tumor progression and chemoresistance via KRAS. Targeting the SPP1-KRAS axis may help overcome chemotherapy resistance in CC.